Telisik Akar Determinan Kinerja Karyawan - Wahyu Nungki Nuraini; Teguh Ariefiantoro (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2022)
The research problem is that employees are not able to achieve the targets set by PT. Bernike International Rubber Processing Industry. This study aims to analyze the influence of leadership, competence, work environment and intrinsic motivation on employee performance. The population is 715 employees, while the sample method is a non-probability sampling method with a purposive sampling type that produces a number of 74 respondents and the analytical tool used is multiple linear regression. The results showed that leadership, competence, work environment and intrinsic motivation had a positive and significant effect on employee performance. The coefficient of determination test results obtained 0.570 (57 percent) employee performance variables can be explained by the variables of leadership, competence, work environment and intrinsic motivation and the remaining 0.430 (43 percent) explained by other variables outside of this study.